PROBIOTICS - A PROBABLE THERAPEUTIC AGENT FOR SPONDYLOARTHROPATHY - Singh, Nandini (Int J Probiotics Prebiotics, 2017)
Spondyloarthropathy (SpA) or spondyloarthrosis refers to any joint disease of the vertebral column. Among the entities of SpA, ankylosing spondylitis has drawn the attention of some researchers, because of its specific mechanism of disease progression. It has been studied earlier that its progression is due to the presence of HLA (human leukocyte antigen) - B27. It shows molecular similarity and immunological cross-reactivity with some of the gut microbiome. Since SpA could be treated or its symptoms could be lessen by medications, but medications itself show many side effects and other complications. Probiotic- being the natural product has been found to be effective against many SpA entities, including Ankylosing Spondylitis. It alters gut microflora somehow in such a way that it helps in reducing the predisposition of any factor to SpA. Here we consider the complex relationship between SpA pathogenesis and gut microbes; with discussion that how use of probiotics as an alternative drug therapy may treat or reduce the progression of SpA, which could be a better future target to treat SpA entities.